Interpreting important health‐related quality of life change using the Haem‐A‐QoL. (31st March 2015) - Wyrwich, K. W.; Krishnan, S.; Poon, J. L.; Auguste, P.; von Maltzahn, R.; Yu, R.; von Mackensen, S.
Summary The Haemophilia Quality of Life Questionnaire for Adults (Haem‐A‐QoL) measures health‐related quality of life (HRQoL) in adults with haemophilia; however, change score thresholds for identifying individuals experiencing a HRQoL benefit have not been appropriately investigated. The objective of this analysis was to derive appropriate HRQoL responder definitions (RDs) for two Haem‐A‐QoL domains that reflect key impairments, 'Physical Health' and 'Sports & Leisure, ' and the Haem‐A‐QoL 'Total Score' using anchor‐ and distribution‐based methods. In this analysis, data from adults in A‐LONG and B‐LONG, two Phase 3 clinical studies of rFVIIIFc in haemophilia A and rFIXFc in haemophilia B, respectively, were used. The anchor‐based approach identified Haem‐A‐QoL changes corresponding to EQ‐5D item improvements between baseline and 6 months; the distribution‐based methods examined the magnitude at baseline of one‐half standard deviation and the standard error of measurement. Through triangulation, the most appropriate RDs were derived. Of the 133 A‐LONG and 73 B‐LONG subjects with baseline Haem‐A‐QoL scores, 67 and 51 subjects, respectively, completed the Haem‐A‐QoL questionnaire at both baseline and 6 months follow‐up. Triangulation of anchor‐ and distribution‐based estimates with the observed Haem‐A‐QoL change scores identified a 10‐point reduction in the 'Physical Health' and 'Sports & Leisure' domains, and a 7‐point reduction in 'Total Score' as the RD thresholds most indicative of HRQoL benefit. These empirically derived RDs for two key Haem‐A‐QoL domains and 'Total Score' are reasonable and practical thresholds for identifying subjects with notable improvements in HRQoL, and provides HRQoL RDs that can be used for further analysis and interpretation of data from haemophilia clinical trials.